Traditional agricultural knowledge in land management: the potential contributions of ethnographic research to climate change adaptation in India, Bangladesh, Nepal, and Pakistan. (9th August 2021) - Rivera-ferre, M.G.; Di Masso, M.; Vara, I.; Cuellar, M.; López-i-Gelats, F.; Bhatta, G. D.; Gallar, D.
ABSTRACT: Land supplies multiple goods and services vital to humans and the environment. In the last decades, increasing evidence of growing land degradation are made apparent. A limited and depleting resource base, the reliance on climate-sensitive sectors and its large population, make South Asia highly vulnerable to climate change. Observed changes in climate include increases in temperature and increased monsoon variability and rainfall pattern leading to drought and flooding. Projected changes include increasing temperatures, rising sea levels, increasing cyclonic activity and higher variability of rainfall, all having enormous impacts on farming communities. At the same time, the region is rich in traditional agricultural knowledge (TAK), specialized in managing local agroecosystems to ensure food availability, tackling climatic risks and other ecological uncertainties. Particularly relevant is TAK related to land management to preserve soil fertility and avoid soil erosion. Ethnographic research is a valuable source of TAK, although this is rarely analysed with a climate change perspective. Based on a qualitative systematic review, and an expert's on-line survey, in this paper we review land management TAK and assess its potential for climate change adaptation. The review shows there is a vast amount of untapped TAK ethnographic research with potential for climate change adaptation.